Hardiness dan Dukungan Sosial Orang Tua dengan Academic Stress di SMK Negeri 1 Way Panji - Nur Septri Lestari; Dian Kinayung (Empathy : Jurnal Fakultas Psikologi, 2022)
Hardiness and Social Support of Parents with Academic Stress at SMK Negeri 1 Way Panji This study aims to examine the relationship between hardiness and parental social support with student academic stress during the COVID-19 pandemic at SMK Negeri 1 Way Panji. The method used is correlational quantitative with a sample of 79 students. Data analysis using multiple regression processed using SPSS 21.0 for Windows. The results of the analysis of the major hypotheses show that there is a very significant relationship between hardiness and parental social support with academic stress. The score R = 0.569 with p value = 0.000 (p < 0.01). The results of the first minor hypothesis analysis show that there is a very significant negative relationship between hardiness and academic stress, if parents' social support is controlled, with a score of r= -0.406, p= 0.000 (p<0.01). The results of the second minor hypothesis analysis show that there is no relationship between parental social support and academic stress. By controlling for hardiness, the score r= -0.026, p= 0.821 (p>0.05). Based on the results of data analysis, it can be concluded that hardiness and social support are jointly correlated with academic stress. However, after analyzing the correlational test for each independent variable by controlling for other variables, the result is that only hardiness has a correlation with academic stress.